Singapore Management University Report to Stakeholders 2019 - 2020 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2020)
The title, "Strength, Unity, Resilience, Purpose", reflects how the University has responded as "One SMU" to the challenges arising from the Covid-19 pandemic. Whilst putting the safety and wellbeing of students, faculty and staff first, SMU pivoted quickly to ensure that it continued to fulfil its role in nurturing global citizens for tomorrow through transformative education, addressing societal challenges through cutting-edge research, and engaging with the city and world to make meaningful impact in a time of crisis. The theme of the report also echoes Professor Lily Kong's inaugural President's State of the University Address in September 2019. In this address, titled "ur Journey of Purpose", she made a rallying call for SMU to drive forward into its third decade by focussing on engaging industry, stimulating innovation, pursuing internationalisation and driving integration. Considering the disruption caused by the pandemic since the second term of the Academic Year, the number and standard of achievements by our students, faculty and staff members in a wide variety of fields, impressive global rankings, strong support for university advancement and several prestigious thought leadership events is remarkable. This publication also includes for the third year running a Sustainability Report which records the solid results of efforts to save energy and water, reduce wastage and create a work and study environment that promotes well-being. For example, SMU Connexion, which opened in January 2020, is the city centre's first large-scale mass engineered timber development and on-site net zero energy building, with its own power generated from a photovoltaic system.